2016
DOI: 10.1039/c6dt01750a
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected reactivity of an alkylaluminum complex of a non-innocent 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene ligand (dpp-bian)

Abstract: The reaction of (dpp-bian)AlEt(EtO) (1) (dpp-bian = 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene) with 4,4'-dimethoxybenzophenone leads to the replacement of EtO with the ketone resulting complex (dpp-bian)AlEt[O[double bond, length as m-dash]C(4-MeOCH)] (2). The reaction of compound 1 with 2,6-di-tert-butyl-4-methylphenol (1 : 1) or PhNH (1 : 1) affords the addition products [dpp-bian(H)]AlEt[O(2,6-tBu-4-MeCH)] (3) and [dpp-bian(H)]AlEt(NPh) (4) correspondingly. Treatment of complex 1 with 0.5 molar equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…One can conclude that the rigid dpp-Bian ligand serves well for stabilization of the Al−C bond. Such a behavior was recently reported 104. These led to reduction of the cationic activator [Ph 3 C][B(C 6 F 5 ) 4 ] instead of Al−C bond cleavage.…”
supporting
confidence: 57%
“…One can conclude that the rigid dpp-Bian ligand serves well for stabilization of the Al−C bond. Such a behavior was recently reported 104. These led to reduction of the cationic activator [Ph 3 C][B(C 6 F 5 ) 4 ] instead of Al−C bond cleavage.…”
supporting
confidence: 57%
“…10 The Berben group observed aluminum-ligand cooperative addition of phenol, benzyl alcohols, 13 water, 14 and formic acid 15 to their bis(iminopyridine)-ligated aluminum hydride. 16 Other examples of aluminum-based cooperative OHaddition reactions were provided by Fedushkin 17 and recently by Zhu. 18 The formal oxidative addition of ROH to phosphorus(III), likely assisted by ELC, was reported for structurally constrained systems by Goicoechea 19 and Dobrovetsky.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that in alkylaluminum complexes, the dpp-Bian is acting rather as stabilizing ligand toward alkyl–aluminum bond. For instance, Ph 2 CO and PhCCH do not insert into the Al–C­(Et) bond in compound (dpp-Bian 2– )­AlEt­(Et 2 O): the ketone replaces the coordinating solvent, while the alkyne forms the cycloadduct through the formation of C–C and C–Al bonds . The situation seems to be similar to gallium hydrides 1 and 4 .…”
Section: Discussionmentioning
confidence: 93%